Temperature-dependent optical functions of selected Ge-Sb-Se bulk chalcogenide glasses obtained by spectroscopic ellipsometry - Janíček, Petr; Chahal, Radwan; Nazabal, Virginie; Němec, Petr (Elsevier Science, 2024)
In this paper, we present spectroscopic ellipsometry measurements of five selected bulk chalcogenide glasses (Ge28Sb6Se66, Ge19Sb17Se64, Ge12Sb25Se63, Ge28Sb12Se60 and As40Se60) for broad wavelength range (0.3-15 mu m) at the temperatures from room temperature up to glass transition temperature (with reserve). Temperature dependence of bandgap energy obtained from Tauc-Lorentz oscillator together with temperature dependence of refractive index for selected wavelengths (1.55, 3.4, 7.0 and 10.6 mu m) where the studied materials are transparent are presented together with thermo-optic coefficients dEg/dT and dn/dT for these wavelengths.
Teplotní závislosti optických funkcí vybraných objemových chalkogenidových skel se složením Ge-Sb-Se získané spektroskopickou elipsometrií
Keywords: Spectroscopic ellipsometry; Temperature dependence; Optical properties; Bulk chalcogenide glasses; Ge-Sb-Se; Spektroskopická elipsometrie; Teplotní závislosti; Optické vlastnosti; Objemová chalkogenidová skla; Ge-Sb-Se